Fotografia e audiovisual de moda: espaços de convívio e ativações de corposmídia para além das mídias - Ortiz, Rogério D'Avila (2022)
This thesis was born from artistic experiments with the designers João Pimenta, Fernanda Yamamoto, Romero Sousa, Donna Liu, Marlene Leopoldino and people who work outside the scope of fashion (students, choreographers, etc.). The main proposal was to ask how processes of creation in fashion, crossed by the arts of the body, can emancipate rather than discipline the bodies, exposing their singularities. The hypothesis that guide this research is that the photographic language does not produce images suspended in time, but has the ability to constitute subjectivities and movements activating micropolitics, states of presence and new spaces of conviviality. As a theoretical foundation, we have created a network of authors who researched bodies (e.g.: KATZ and GREINER, 2005; VIGARELLO and COURTINE, 2008; FOUCAULT, 1975); fashion (e.g: GOES and VILLAÇA 1998, CASTILHO 2005, MESQUITA, 2004, 2011, 2017); and some topics of political philosophy, such as debates on collectives, gestures and artfulness (MASSUMI, MANNING 2015). The practical methodology was based on photographic essays, artistic residencies and teaching/learning propositions about body, photography and fashion audiovisual. In addition to the thesis, we have built a website that presents starting points of the research around the gestation (of the work and one life) and gathers documentation around the artistic residency with Vera Sala and João Pimenta; research with Fernanda Yamamoto on Slow Fashion, an immersion in Cariri Paraibano with women and the presentation of a campaign on breastfeeding associated with the translactation technique. The set of experiences should not be interpreted as an illustration of the thesis, but as a way of problematizing the main issues proposed. Part of the content of this site has been handwritten and each element published has its audiodescription and interpretation in Libras